A novel core–shell structure of CuNW@PSS accelerates the process of methane hydrate formation. (1st January 2023) - Rong, Wenlian; Zhang, Yu; Luo, Shengjun; Guo, Rongbo
Graphical abstract: Highlights: A novel core-shell structure of copper nanowires coated with sulfonate polymer (CuNW@PSS) synthesized in this work. The CuNW@PSS has better wettability than PSS in methane hydrate experiments. The recycling value of CuNW@PSS has been proved by multiple methane hydrate formation and decomposition experiments. Abstract: Considering the high thermal conductivity of copper material and the promoting effect of sulfonate ions on methane hydrate formation, in this study, copper nanowires coated with sulfonate polymer (CuNW@PSS) were used in methane hydrate experiments. The morphology of synthesized CuNW@PSS was confirmed by SEM and TEM, and the composition was analyzed by elemental analysis, it has clearly core–shell structure. The surface wettability of the material changed from hydrophilic to hydrophobic after sulfonate modification. In methane hydrate formation experiments, compared with PSS, CuNW@PSS can shorten the induction time by 78.5 %, from 61.87 ± 21.71 min to 13.28 ± 5.47 min, the growth rate increased by 130 %, from 0.6 ± 0.13 mmol/min to 1.38 ± 0.34 mmol/min. In addition, CuNW@PSS has good cycling and defoaming performance in the multi-cycle methane hydrate formation and dissociation experiments, which would have potential application for natural gas storage and transportation.